The Correlation Between White Matter Hyperintensity Burden and Regional Brain Volumetry in Patients With Alzheimer's Disease - Cao, Zhiyu; Mai, Yingren; Fang, Wenli; Lei, Ming; Luo, Yishan; Zhao, Lei; Liao, Wang; Yu, Qun; Xu, Jiaxin; Ruan, Yuting; Xiao, Songhua; Mok, Vincent C. T.; et al. (Frontiers in Human Neuroscience, 2022)
Background: White matter hyperintensities (WMHs) and regional brain lobe atrophy coexist in the brain of Alzheimer’s disease (AD) patients, but the association between them in AD patients still lacks comprehensive investigation and solid imaging data support. Objective: We explored whether WMHs can promote the pathological process of AD by aggravating atrophy in specific brain regions and tried to explain the regional specificity of these relationships. Methods: A sample of 240 adults including 180 normal controls (NC) and 80 AD cases were drawn from the ADNI database. T1-weighted Magnetic Resonance Imaging (MRI) and T2-weighted fluid-attenuated MRI of the participants were downloaded and were analyzed using AccuBrain® to generate the quantitative the ratio of WMHs (WMHr, WMHs volumes corrected by intracranial volume) and regional brain atrophy. We also divided WMHr into periventricular WMHr (PVWMHr) and deep WMHr (DWMHr) for the purpose of this study. The Cholinergic Pathways Hyperintensities Scale (CHIPS) scores were conducted by two evaluators. Independent-t test, Mann-Whitney U test or χ2 test were used to compare the demographic characteristics and Spearman correlation coefficient values were used to determine the association between WMHs and different regions of brain atrophy. Results: Positive association between WMHr and quantitative medial temporal lobe atrophy(QMTA) (rs=0.281, p=0.011), temporal lobe atrophy (rs=0.285, p=0.011), insular atrophy (rs=0.406, p<0.001) were found in the AD group before Bonferroni correction. PVWMHr contributed to these correlations. Separately analyzed the relationship between PVWMHr and brain atrophy, we found there were still positive correlations after correction in QMTA (rs=0.325, p=0.003), temporal lobe atrophy (rs=0.298, p=0.007) and insular atrophy (rs=0.429, p<0.001) in AD group. Conclusions: WMHs severity are tend to associated with regional brain atrophy in AD patients, especially with medial temporal lobe, temporal lobe and insular lobe atrophy. PVWMHs were devoted to these correlations.